2019
DOI: 10.1111/pcmr.12764
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling activation induces cell death in MAPKi‐resistant melanoma cells

Abstract: The role of Notch signaling in melanoma drug resistance is not well understood. In this study, we show that although NOTCH proteins are upregulated in metastatic melanoma cell lines, Notch signaling inhibition had no effect on cell survival, growth, migration or the sensitivity of BRAFV600E‐melanoma cells to MAPK inhibition (MAPKi). We found that NOTCH1 is downregulated in melanoma cell lines with intrinsic and acquired resistance to MAPKi. Forced expression of NICD1, the active form of Notch1, caused apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The Notch family receptors are involved in regulating the development, differentiation, and cellular function of multiple cell types [45][46][47][48][49]. In particular, the Notch1 signaling pathway has demonstrated a close relationship with melanoma progression [40,41,[50][51][52][53][54][55]. For example, studies have proven that Notch1 signaling promotes the progression of primary melanoma through activation of mitogen-activated protein kinase/phosphatidylinositol 3-kinase-Akt pathways and upregulation of N-cadherin expression [56].…”
Section: Discussionmentioning
confidence: 99%
“…The Notch family receptors are involved in regulating the development, differentiation, and cellular function of multiple cell types [45][46][47][48][49]. In particular, the Notch1 signaling pathway has demonstrated a close relationship with melanoma progression [40,41,[50][51][52][53][54][55]. For example, studies have proven that Notch1 signaling promotes the progression of primary melanoma through activation of mitogen-activated protein kinase/phosphatidylinositol 3-kinase-Akt pathways and upregulation of N-cadherin expression [56].…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate that the higher expression of RPS6 , TP53 , NOTCH1 and ABL1 observed in regressed melanomas could be associated with a more preserved cell cycle control, apoptosis and proliferation 4,5,6 …”
Section: Total (96) Control Group (50) Regression Group (46) Pmentioning
confidence: 99%
“…Although RBP-J is accepted as the major effector for the canonical Notch, RBP-J independent non-canonical Notch signaling has also reported [17]. Notch signaling is known to contribute to melanoma progression [18], acting both as a tumor promoter or suppressor depending on the cellular context [19][20][21][22]. Mikheil et al showed that forced expression of NICD, the active form of Notch, was sufficient to induce apoptosis independently of MAPK pathway inhibition in melanoma cells, with both intrinsic and acquired resistance to MAPK inhibitors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Notch signaling is known to contribute to melanoma progression [18], acting both as a tumor promoter or suppressor depending on the cellular context [19][20][21][22]. Mikheil et al showed that forced expression of NICD, the active form of Notch, was sufficient to induce apoptosis independently of MAPK pathway inhibition in melanoma cells, with both intrinsic and acquired resistance to MAPK inhibitors [21]. Considering the oncogenic role of Notch1 signaling in melanoma, a phase II trial using broad Notch signaling inhibitors surprisingly only showed minimal clinical activity against metastatic melanoma [19].…”
Section: Introductionmentioning
confidence: 99%